13C surface characterization of midplane and crown collector probes on DIII-D. (March 2023) - Duran, J.D.; Donovan, D.C.; Nichols, J.H.; Unterberg, E.A.; Zamperini, S.A.; Abrams, T.; Perillo, R.; Ren, J.; Rudakov, D.L.; Shafer, M.W.; Stangeby, P.C.; Taussig, D.A.; et al.
Highlights: Dual collector probe system developed for increasing poloidal resolution of SOL impurities. Basic stable isotopic mixing model developed for carbon-12 and carbon-13 isotopes. Enriched deposits from a methane puff and a re-eroded wall source measured with collector probes. Abstract: A dual collector probe system has been implemented on DIII-D for scrape-off-layer (SOL) impurity transport studies. These experiments injected isotopically enriched methane ( 13 CD4 ) and sampled the impurities from this extrinsic, primary source with graphite collector probes at the outboard midplane and crown of upper single null L-mode plasmas. Using a stable isotopic mixing model, results suggest that 13 C from methane injections prior to these experiments has built up on the walls of DIII-D to act as a secondary, intrinsic source of enriched 13 C to the collector probes. This secondary source accounts for nearly 60 % of the deposits on the midplane collector probes and nearly 90 % of the deposition on the collector probes in the crown. These results lay the foundation for future impurity transport models and suggest that further simulation of impurity transport during the methane injection experiments will require two sources of enriched impurities in order to accurately model the SOL impurity profiles of 13 C.